SISTEM INFORMASI PENJUALAN OBAT PADA APOTEK DEMANGSARI BERBASIS WEB - JOKO PURNOMO; NOVITA SETIANTI; NOVIA SURYATININGSIH (LPPM STMIK Widya Utama, 2023)
Abstract - Medicines are all single ingredients or mixtures that are used by all creatures for the inside and the outside, to prevent, relieve, or prevent disease. Apotek Demangsari is a pharmacy that is engaged in drug sales, the system that is running at Apotek Sakti uses a manual system so that it often has problems with calculations, information validation, slow transactions, difficulties in making reports manually so they often have problems with calculations, information validation, Therefore, in this study, a sales information system was built at a webbased Demangsari pharmacy that can display drug sales reports and the amount of drug stock in the warehouse that can be accessed by employees, so that employees can come together and find out how many drugs will be ordered and purchased for supplies. In its development, this mobile application applies a prototyping method which consists of several steps, namely identifying basic needs, developing initial prototypes, user reviews, and repairing and developing prototypes. This mobile application is tested using the Black Box Testing product test method which is valid and reliable. The results of this study are in the form of an information system to handle input data and then manage the amount of stock that can be checked regularly both daily, daily and monthly. From the recapitulation of product test scores and benefit tests, the percentage of Useability is 86%, Learnability is 93%, Efficiency is 97.5%, Acceptability is 93.25% and the highest percentage is in the aspect of Efficiency, which states that this mobile application is easy to use by pharmacy employees and students.